ENTREPRENEURSHIP ISLAM SUATU JALAN ALTERNATIF: TINJAUAN EPISTEMOLOGI - Darmadi; Hoir, Hubul (LPPM UIN Sulthan Thaha Saifuddin Jambi, 2024)
Entrepreneurship is a vital foundation to economic development of a country. This is parallel to Islamic religion which en courage Muslim to get involped in entrepreneurship. This article attempts to review the concept of Islamic entrepreneurship and its implementations in nation development. The article concludes is the most effective mechanism in cultivating the culture of Islamic entrepreneurship among Muslims.